Urine protein excretion and swimming events - Poortmans, J. R.; Engels, M. F.; Sellier, M.; Leclearcq, R. (Medicine & Science in Sports & Exercise, 1991)
Some of the kidney's responses to different swimming exercises were measured in 12 trained males. Protein excretion was analyzed. It was found that an increase in swimming intensity induces an increase in glomerular membrane permeability and an impaired tubular reabsorption. Increased swimming intensity appears to be the prevalent stimulus for transient renal dysfunction. The features of the dysfunction are i) reduced plasma volume, and ii) enhanced protein excretion rate.